Analysis of loads, motions and cavity dynamics during freefall wedges vertically entering the water surface. (June 2015) - Wang, Jingbo; Lugni, Claudio; Faltinsen, Odd Magnus
Abstract: In this paper, theoretical models are developed and numerical methods are used to analyze the loads, motions and cavity dynamics for freefall wedges with different deadrise angles vertically entering the water surface at Froude numbers: 1 ≤ Fn < 9. The time evolutions of the penetration depth, the velocity and the acceleration are analyzed and expressed explicitly. The maximum and average accelerations are predicted. The theoretical results are compared with numerical data obtained through a single-fluid BEM model with globally satisfactory agreement. The evolution of the pressures on the impact side is investigated. Before flow separation, gravity and the acceleration of the wedge have negligible influence on the pressure on the impact side for large Froude numbers or small deadrise angles; with increasing the deadrise angle or decreasing Froude number, the effects of gravity and the acceleration of the wedge tend to become more important. Global loads, with the main emphasis on the drag coefficient, are also studied. It is found that for the light wedge, the transient drag coefficient has slow variation in the first half of the collapse stage and rapid variation in the last half of the collapse stage. For the heavy wedge, the transient drag coefficients vary slowly during the whole collapse stage and can be treated as constant. The characteristics of the transient cavity during its formation are investigated. The non-dimensional pinch-off time, pinch-off depth and submergence depth at pinch-off scale roughly linearly as the Froude number.